Reasons that affect the sports retirement of handball players from the Asobal League - Jose Cuenca; Ana María Gallardo; Carlos Chavarría-Ortiz; Rafael Baena-González (Motricidade, 2025)
All professional athletes have to face retirement from professional sports at least once in their lives. Handball is a minority sport, and the majority of athletes have to continue their working life outside of the sport once they retire. The objective of this work was to analyse how the reasons for withdrawal influence variables such as the level of education, professional situation, marital status, number of children and the voluntariness of retiring in the sports retirement process. The sample comprises 95 professional handball players, 100% male, who retired in the last 10 years in the Spanish handball league, Liga ASOBAL. They have been administered a validated questionnaire. A descriptive, relational and transversal study has been carried out to analyse the results obtained from the questionnaire. Work reasons are the ones that most influence the withdrawal of professional handball players. Adequate planning and anticipation of this episode are fundamental factors in obtaining a successful result.